Democracy for Sale : Elections, Clientelism, and the State in Indonesia - Aspinall, Edward; Berenschot, Ward (Book collections on Project MUSE., 2019)
"Written on the basis of extensive fieldwork and survey research, Democracy for Sale shows how Indonesian politics is built around the exchange of cash, goods and favors, and organized through informal relationships and networks rather than parties and formal institutions"--